A 10-Month-Old Infant Presenting With Signs of Precocious Puberty Secondary to a Sclerosing Stromal Tumor of the Ovary in the Absence of Hormonal Elevation. (July 2019) - Squillaro, Anthony I; Zhou, Shengmei; Thomas, Stefanie M; Kim, Eugene S
Precocious puberty in an infant is an alarming and infrequent finding, making the differential diagnosis difficult for practitioners. Precocious puberty secondary to a sclerosing stromal tumor (SST) of the ovary is rare. We present a case of a child that began precocious puberty at 3 months of age including development of breast buds, pubic hair, growth spurt, and menarche 5 days prior to presenting to pediatric endocrinology at 10 months. She underwent right salpingo-oophorectomy which demonstrated a soft tissue mass occupying almost the entire ovary with a tan-pink fleshy cut surface. Histological examination confirmed a variant of SST. This case represents an extremely young onset of precocious puberty secondary to a variant of SST without hormonal elevation.